Edukasi kesehatan kepada orangtua melalui asuhan keperawatan keluarga dalam pencegahan stunting pada balita - Dava Arya Putra; Rudi Winarno; Eka Trismiyana (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Stunting is a chronic nutritional issue that impacts child growth and development. According to the WHO (2023), 148 million children under five worldwide suffer from stunting. In Indonesia, the stunting prevalence was 21.6% in 2022; in Lampung Province, it was 15.9% in 2024; and in Bandar Lampung City, it was 14.8%, with 27 cases recorded in the Panjang Community Health Center area. Health education for parents serves as a stunting prevention strategy by improving knowledge and behaviors regarding the fulfillment of children's nutritional needs. Therefore, nursing care focused on stunting prevention for children under five delivered through health education for parents was implemented at the Panjang Community Health Center in Bandar Lampung City in 2026. Purpose: To provide direct education through nursing care to parents regarding stunting prevention. Method: This activity involved nursing care using a case study approach, conducted from January to February 2026 at the Panjang Community Health Center, Bandar Lampung City. The population consisted of 14 families with children under five showing indications of stunting. Through purposive sampling, two families with children diagnosed with stunting and for whom the nursing diagnosis was